The Development of Leading Product through Incubation Program in Rural Development, Riau Province - Kurnia Novianti; Saiful Hakam (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2014)
Rural areas, as the areas that have been the most targeted and developed in Indonesia, become the places of interest for social research. A case in Riau revealed that among many natural resources that can be developed, palm oilis still becoming the most attention leading product by local government. This paper is to describe the concept of leading product and its relation with rural development through incubation program that have been activatited in that province. This paper also propose a recomendation to the implementors of the program activities with more bottom-up approach, with capacity owned by community so that the their commitment in the development process will be optimum. Analysis in this papaer will be based on field research conducted in 2013 and literature studies from various resources.